Investigation of physiological responses of Procambarus clarkii and some enzyme activities to selected heavy metals - Hussein AB; A Abbas; N Hussein; Noreldaim Elkhidir (Open Journal of Environmental Biology - Peertechz Publications, 2019)
Mean enzyme activities of Aspartate Transaminase (ALT), Aka Alanine Transaminase (AST) and alkaline phosphatases of the digestive gland of freshwater Procambarus clarkia were subjected to different sublethal concentrations of lead, mercury and cadmium were measured.